(untitled) (Palíndromo, 2013)
When Frederico Morais organized the events in Flamengo t embankment, the proposal was already, like Helio Oiticica, to eliminate the gap between contemporary art, its social meaning and the urban masses. Approaching people of art, the art of life, was one of the goals of the events that marked the demarche of neovanguards the years 1960 and 1970. In the specific case of the arts, the object - as artistic category - had gained importance in the communication of visual languages and became a key element to the exhibition Object and Participation in the Palace of Arts on April 17, 1970. Along with the exhibition, Morais thought performing art forms (art experiential, conceptual or ephemeral and so on.) within the Municipal Park of Belo Horizonte, known as Do corpo à terra, between 17 and 21 April 1970.